Do plant traits explain tree seedling survival in bogs?. (12th September 2013) - Limpens, Juul; van, Emily; Li, Bingxi; Holmgren, Milena; Allen, Edith
Summary Moss‐dominated peat bogs store approximately 30% of global soil carbon. A climate induced‐shift from current moss‐dominated conditions to tree‐dominated states is expected to strongly affect their functioning and carbon sequestration capacity. Consequently, unravelling the mechanisms that may explain successful tree seedling establishment in these ecosystems is highly relevant. To assess the role of drought on early tree seedling establishment and the relative importance of plant traits in tree seedling survival, we conducted a factorial glasshouse experiment with seven conifer species. Our results show that drought inhibits moss growth, thereby increasing survival of tree seedlings. Survival success was higher in Pinus than in Picea species, ranking Pinus banksiana > Pinus sylvestris > Pinus nigra > Picea mariana > Picea glauca, Picea sitchensis > Picea rubens. We found that those species most successful under dry and wet conditions combined a fast shoot growth with high seed mass. We conclude that plant traits contribute to explaining successful early tree seedling establishment in bogs.